Cloaked Caged Compounds: Chemical Probes for Two‐Photon Optoneurobiology. Issue 1 (2nd December 2016) - Richers, Matthew T.; Amatrudo, Joseph M.; Olson, Jeremy P.; Ellis‐Davies, Graham C. R.
Abstract: Caged neurotransmitters, in combination with focused light beams, enable precise interrogation of neuronal function, even at the level of single synapses. However, most caged transmitters are, surprisingly, severe antagonists of ionotropic gamma ‐aminobutyric acid (GABA) receptors. By conjugation of a large, neutral dendrimer to a caged GABA probe we introduce a "cloaking" technology that effectively reduces such antagonism to very low levels. Such cloaked caged compounds will enable the study of the signaling of the inhibitory neurotransmitter GABA in its natural state using two‐photon uncaging microscopy for the first time. Abstract : Caged neurotransmitters are known to be antagonistic toward the GABA‐A receptor. Conjugation of a polyester dendrimer "cloak" to the caged compound DEAC450‐GABA significantly decreased its GABA‐A receptor antagonism. The chemical probe was inert at the concentrations required for effective two‐photon photolysis on living cells.